Rethinking Debt: Theology, Indebted Subjects, and Student Loans. Issue 1 (March 2016) - Phelps, Hollis
Abstract: This article focuses on the way in which a theological understanding of debt resonates with moral and economic debt, with particular attention paid to student loan debt. Although the so‐called satisfaction theory of atonement, which grounds itself in the debt we owe to God, resonates with the logic of contemporary capitalism, this article suggests that other theological traditions concerning debt, which conceive of debt variously as something owed to the devil or as something that God owes to us, provide avenues for rethinking debt, theologically, morally, and economically.